Pelatihan Keterampilan Dasar Mengajar Bagi Guru Tugas Pondok Pesantren Syekh Abdurrahman Rabah - Ainur Rofiq Hafsi; Laili Amalia; Ukhti Raudhatul Jannah; Harsono Harsono; Qudsi Ali; Fazaraul Farahiyyah Ad-Daimah (Institut Teknologi dan Bisnis Semarang, 2023)
The problem faced by Sheikh Abdurrahman Rabah Islamic Boarding School is that there is a lack or limitation in the teaching skills of the task teachers. They have strong religious knowledge, but lack knowledge or experience in effective teaching methods. This can affect the quality of learning in the pesantren and the teachers' ability to deliver material clearly and interestingly. Training on basic teaching skills can help teachers deliver the material more effectively, manage the class well, and improve interaction with the students. The stages of implementing this service activity include: identifying the specific needs of prospective task teachers by conducting surveys or interviews with prospective task teachers to understand their needs in developing teaching skills, creating a training program framework for effective teaching methods, classroom management, use of educational technology, and learning evaluation, preparing a training schedule and arranging the necessary venues and facilities, providing training materials, including materials, tasks, and other supporting resources, carrying out training activities in the form of materials and practices of effective teaching methods, classroom management, use of educational technology, and learning evaluation, and carrying out evaluation of training activities. The results of the implementation of this service activity are: understanding and accuracy in selecting and applying methods that can be applied to schools in the pesantren environment, participants understand and apply how to manage the classroom by improving classroom discipline, increasing time efficiency, creating a positive learning environment, increasing student involvement, improving communication skills, improving student achievement, and managing student diversity, participants are able to independently and skillfully create learning media by utilizing AI. Participants are able to create PPT easily using AI, participants are able to provide feedback to students, identify areas that need improvement during the learning process, and measure students' final achievement on a topic or learning period. In addition, participants were able to practice conducting mini exams, class discussions, oral questions, daily assignments, midterms, and final exams.